CMOS Compatible Plasmonic Refractive Index Sensor based on Heavily Doped Silicon Waveguide - Faruque, M. O.; Al Mahmud, R.; Sagor, R. H. (Engineering, Technology & Applied Science Research, 2020)
In this study, a plasmonic refractive index (RI) sensor using heavily n-doped silicon waveguide is designed and numerically simulated using finite element method (FEM). The reported sensor is based on gratings inside a heavily doped silicon waveguide structure instead of a conventional metal-insulator-metal structure. This feature enables the device to overcome the limitations of conventional plasmonic devices like optical losses, polarization management, etc. Besides, it makes the device compatible with Complementary Metal Oxide Semiconductor (CMOS) technology and thus provides an easier way of practical fabrication and incorporation in integrated circuits. The presented sensor has a highest sensitivity of 1208.9nm/RIU and a resolution as small as 0.005 which is comparable with conventional plasmonic sensors reported to date. The main advantage of this plasmonic sensor is that it has a very simple structure and uses silicon instead of metal which provides an easier way of fabrication.